Study of the Biological Activities of Aethiopinone Isolated from the Hexane Extract of Salvia argentea L. Roots and its Combinations with Reference Products - Ziane, Safaa Nour El Houda; Dib, Mohammed El Amine; Bensaid, Okkacha; Muselli, Alain (Current Bioactive Compounds, 2026)
BackgroundIn recent years, chemical and biological studies have explored medicinal plants to develop new treatments for oxidative stress, inflammation, and diabetes.ObjectiveThis study aims to characterize for the first time the chemical composition of the hexane extract from the roots of Salvia argentea using GC and GC/MS techniques. We also isolated its major compound and evaluated its biological activities, including its antioxidant, anti-inflammatory, antidiabetic, and hemolytic effects, as well as the combination of this major compound with reference drugs.MethodsAntioxidant activity was assessed using DPPH, β-carotene, and phosphomolybdenic tests. The anti-inflammatory effect was measured by the egg albumin denaturation method and protein denaturation inhibition. The antidiabetic activity was determined by evaluating the inhibition of α-amylase, with acarbose as a positive reference. The combined effect of aethiopinone with standards was also studied to reduce the minimum effective dose and minimize side effects.ResultsThe hexane extract of Salvia argentea is mainly composed of aethiopinone (53.3%) and ferruginol (20.5%). aethiopinone was isolated and identified using spectroscopic methods, including 1H NMR, 13C NMR, and IR. The biological activity assessment showed that hexane extract and aethiopinone had promising antioxidant, anti-inflammatory, and antidiabetic properties. In addition, synergistic effects were observed when aethiopinone was combined with positive references, resulting in a significant reduction of the required minimum inhibitory concentrations. The human erythrocyte toxicity assessment showed that hexane extract and aethiopinone induced very low hemolysis levels, reaching 24.18% and 31.13%, respectively, at high concentrations of 2000 μg/mL.ConclusionFurther research is needed to confirm their therapeutic effects and assess their potential for use in the pharmaceutical industry.
Keywords: aethiopinone